Hybridizing an immune artificial algorithm with simulated annealing for solving constrained optimization problems - Aragón, Victoria S. (2011)
In this paper, we present a modified version of an algorithm inspired on the T-Cell model, it is an artificial immune system (AIS), based on the process that suffers the T-Cell. The proposed model (TCSA) is increased with simulated annealing, for solving constrained (numerical) optimization problems. We validate our proposed approach with a set of test functions taken from the specialized literature. We indirectly compare our results with respect to GENOCOP III, a well known software based on genetic algorithm